Comparative Analysis of a Novel Material, GPRA as Partial Replacement in Coarse Aggregate with Individual Materials (International Journal of Innovative Research in Computer Science & Technology, 2023)
GPRA is a unique material made up of  shredded glass, plastic, rubber, and aluminum particles.  Concrete is abundantly used building material on the  planet, requiring around 12.6 billion tons of natural  resources to produce. All of the elements in concrete are  partially or completely replaced by a variety of waste  products, such as fly ash, rice husk ash, wheat straw ash,  and so on. Rapid urbanization and industrialization around  the world has resulted in large amounts of plastic trash and  waste tyre rubber being deposited. This trash can be used to  lower the coarse aggregate content of concrete when used  in the proper conditions. This research work looks at the  potential of a novel compound GPRA i.e. (Glass, Plastic,  Rubber, Aluminum) as a partial replacement in coarse  aggregate. Though there has been enough research on use  of waste materials as replacement in concrete structures  with an aim to curb pollution levels. This research work  aims to utilize properties of waste materials which may  give a higher performance than individually using of waste  materials and while lowering of various pollution levels  with cost effective ways for partial replacement of coarse  aggregates in concrete, shredded waste materials for GPRA  with sizes ranging from 4.75 to 20 mm will be employed.  This investigation will use an M30 design mix with a target  mean strength of 42 n/mm2. GPRA will be used to partially  replace coarse aggregate in the following percentages:  10%, 30%, and 40%. The C.S., S.T.S., and F.S. of GPRA  in hardened concrete has to be compared to the individual  replacement of these waste materials.
Keywords: GPRA; Concrete; Waste Materials; Aggregate Concrete Mixtures